2017
DOI: 10.1155/2017/4926815
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Scopolamine‐Induced Learning and Memory Impairment by α‐Pinene in C57BL/6 Mice

Abstract: Increasing evidence suggests that neurodegenerative disorders such as Alzheimer's disease (AD) are mediated via disruption of cholinergic neurons and enhanced oxidative stress. Therefore, attention has been focused on searching for antioxidant phytochemicals for the prevention and/or treatment of AD through their ability to fortify cholinergic function and antioxidant defense capacity. In this study, we have investigated the neuroprotective effect of α-pinene (APN) against learning and memory impairment induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 39 publications
(32 reference statements)
9
57
0
Order By: Relevance
“…Moreover, learning and memory impairment related to AD arises from damage to cholinergic neurons. Cholinergic deficit has been considered as a marker of neurological pathology that is correlated to memory disturbance and constantly associated with the severity of cognitive disorders in AD . In this research, kainic acid injection significantly increased AChE activity and Hup‐A could reduce the activity of this enzyme.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, learning and memory impairment related to AD arises from damage to cholinergic neurons. Cholinergic deficit has been considered as a marker of neurological pathology that is correlated to memory disturbance and constantly associated with the severity of cognitive disorders in AD . In this research, kainic acid injection significantly increased AChE activity and Hup‐A could reduce the activity of this enzyme.…”
Section: Discussionmentioning
confidence: 73%
“…Further, among the components evidenced in the essential oil from alpine needle leaves of Abies koreana, γ-terpinene exhibited a memory-enhancing effect on Sco-induced amnesia in mice [16]. Lee et al [17] also reported that α-pinene has an ameliorative effect on Sco-induced learning and memory impairment in C57BL/6 mice. These findings indicated that the memory-ameliorating effect of the MO and anti-AChE properties could be attributed to the presence of these compounds.…”
Section: The Chemical Composition Of the Essential Oil MIXmentioning
confidence: 96%
“…Impairment of memory and learning and the foremost characteristic manifestation of psychological feature dysfunction are caused by scopolamine, a cholinergic antagonist which interferes with neurotransmitter transmission within the central nervous system [17,18]. The Fig.…”
Section: Discussionmentioning
confidence: 99%